The effectiveness of collection system in Majlis Bandaraya Melaka Bersejarah (MBMB) / Nur Syuhada Yakop - Yakop, Nur Syuhada (Faculty of Business and Management, 2011)
The Effectiveness of Collection System in Majlis Bandaraya Melaka Bersejarah (MBMB) analyzes the effectiveness of collection system in MBMB before and after using specific system in their collection. Since the MBMB was established, the collection system done manually by using all record keeping in the cash book or in the ledger book. During that time, there is no computerized system being implemented in Municipal Council in Malaysia. All transaction was recorded manually and kept in a specific file. Many problems occurred during that time. Over the time, MBMB began practicing the computerized revenue system which is they used the "e-logins‟ system. The "e-logins‟ helps to improve the effectiveness of collection in MBMB. There was a huge change in revenue after the system being implemented. In this research, I investigate the problems occurred before and after the system being used. Many advantages but there are also disadvantages of the system. I will analyze all the problems and in the last chapter, I would recommend a few ways to improve the collection system in MBMB. I attached with the flowchart of the collection system flow and many more in appendix.